Systemic and Local Biocompatibility Assessment of Graphene Composite Dental Materials in Experimental Mandibular Bone Defect - Alexandra Dreanca (Materials, 2020)
The main objective of this research is to demonstrate the biocompatibility of two experimental graphene dental materials by in vitro and in vivo tests for applications in dentistry. The novel graphene dental materials, including one restorative composite and one dental cement, were subjected to cytotoxicity and implantation tests by using a rat model of a non-critical mandibular defect. In vitro cytotoxicity induced by materials on human dental follicle stem cells (restorative composite) and dysplastic oral keratinocytes (dental cement) was investigated at 37 °C for 24 h. After in vivo implantation, at 7 weeks, bone samples were harvested and subjected to histological investigations. The plasma biochemistry, oxidative stress, and sub-chronic organ toxicity analysis were also performed. The resulting cytotoxicity tests confirm that the materials had no toxic effects against dental cells after 24 h. Following graphene dental materials implantation, the animals did not present any symptoms of acute toxicity or local inflammation. No alterations were detected in relative organ weights and in correlation with hepatic and renal histological findings. The materials’ lack of systemic organ toxicity was confirmed. The outcomes of our study provided further evidence on the graphene dental materials’ ability for bone regeneration and biocompatibility.